Growth analysis and curcumin content of long, medium and short duration turmeric (Curcuma longa L.) genotypes - Y Narayana Reddy, A Manohar Rao, P Venkat Rao, (Journal of Spices and Aromatic Crops, 2006)
Six turmeric (Curcuma longa) genotypes, two genotypes each from long (Armoor andDuggirala), medium (CLI-317 and CLI-330) and short (PCT-13 and PCT-14) duration wereevaluated at Jagtial (Andhra Pradesh). Long duration genotypes accumulated more drymatter and maintained leaf area index, chlorophyll content and cumulative growth rate forlonger period up to 210 days, resulting in higher yield and curing percentage over mediumand short duration genotypes. The long duration genotype Duggirala produced highestfresh rhizome yield (168 g plant-1) and Armoor had highest curing percentage (20.26).Curcumin content was higher in short duration genotypes over medium and long durationgenotypes. Maximum curcumin content was recorded in short duration genotype PCT-14(4.06 %).